Transformed inputs for linearization, decoupling and feedforward control. (February 2023) - Skogestad, Sigurd; Zotică, Cristina; Alsop, Nicholas
Abstract: This paper introduces powerful static input transformations which transform the original system (process) into a transformed system which is easier to control. The transformed inputs (controller outputs) may be implemented in many ways and under many names, for example, as ratio, feedforward and decoupling control, or more generally as nonlinear computation blocks. These methods are frequently used in industry, but are often introduced in an ad-hoc fashion. The present paper provides a systematic method for deriving such control strategies from a nonlinear process model. For a static model, the ideal transformed input is simply the right-hand-side of the model equations. The resulting transformed system is linear, decoupled and independent of disturbances. In some cases, use of extra measurements simplify the input transformation by replacing model equations. It is also possible to derive ideal transformed inputs from a dynamic model, which turns out to be a special case of a nonlinear control approach called feedback linearization. However, except for achieving linearization also dynamically, the benefits of using feedback linearization are small compared to using transformed inputs based on a static model. For implementation we need to invert the input transformation, and for this we may use an exact model-based inverse or an approximate feedback-based inverse. The latter leads to the use of cascade control.